(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The purpose of this article is to show that there was a group of Spanish intellectuals, during the period known as Late Scholastics, who, inserted in a historical context of great world commercial development, produced a significant number of works aimed at explaining the functioning os markets, commercial and financial activities, as well as some original discussions on the legitimacy of interest.